Diversity of medicinal flora and traditional knowledge of Muzaffargarh District Punjab Province, Pakistan - Afzal, Muhammad; Abbas, Zaheer; Noreen, Zahra; Nawaz, Gul; Sajjad, Muhammad; Khan, Shujaul Mulk; Abdullah; Harun, Nida; Yawer, Affiefa (Ethnobotany Research and Applications, 2024)
Background: Ethnomedicine is an important part of different cultures across the globe. It has a central role in providing new medicinal plants to phytochemical exploration and effective drug discoveries for centuries. Methods: Ethnobotanical surveys were conducted to collect the ethnobotanical knowledge. We used a snowball technique for respondents sampling. Semi-structured interviews were for ethnobotanical data collection. Relative frequency citation (RFCs), fidelity level (Fl), Use value (UV), and Informant consensus factor (ICF) were used to analyze the data. Results: A total of 68 medicinal taxa belonging to 64 genera and 39 families. Fabaceae was the dominant family with (7 species,9.7%) followed by Moraceae (5 species, 6.9%) and Myrtaceae, and Cucurbitaceae with (4 species, 5.5%) each. In utilization trees (26) were dominant. Regarding part used leaves (23.61%) were frequently utilized. In Powder was ranked first in crude drug formulation using in (30 medications. In quantitative analysis, the maximum RFCs value was calculated for Azadirachta indica A.Juss. and Phyla nodiflora (L.) Greene. Highest FL100 was % totaled for Capparis decidua Edgew and Triticum aestivum L. Similarly, Jasminum officinale L. and Leptadenia pyrotechnica (Forssk.) Decne. Scored highest UV values. Maximum ICF was recorded for Dental and dermal disorders respectively. Conclusion: The plant-based knowledge of the area is substantial but limited to aged people. Saturating allopathic drugs and rapidly changing life trends have strikingly declined the importance of ethnobotanical resources. Hence, the study urges for the revival and conservation of the ethnobotanical heritage at emergency basis. Key words: medicinal plants, indigenous knowledge, arid lands, phytotherapy, ethnobotany